2020
DOI: 10.3390/medicina56080380
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Pathological and Microbiological Evaluation of Diabetic Foot Syndrome

Abstract: Background and objectives: Diabetic foot ulcer (DFU) is one of the serious complications of diabetes, being related to frequent and long-term hospitalisation, reduced quality of life of the patient, amputations, a high rate of morbidity and mortality. The bacterial aetiology is complex, sometimes involving more than one pathogen, playing a major role in the infection prognosis and development of microbial resistance. This study evaluated the current state of the aetiology, clinical and pathological characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 48 publications
2
19
0
4
Order By: Relevance
“…Similar to the findings of other studies, there was a predominance of men over women in the present study [ 13 ]. It is possible that women have superior diabetic foot awareness, knowledge, and attitudes than men; they have also been found to be less susceptible to diabetic foot according to a cross-sectional study in Saudi Arabia [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to the findings of other studies, there was a predominance of men over women in the present study [ 13 ]. It is possible that women have superior diabetic foot awareness, knowledge, and attitudes than men; they have also been found to be less susceptible to diabetic foot according to a cross-sectional study in Saudi Arabia [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of the participants in this study was 63 years, which is consistent with that found in other studies from different countries [ 12 , 13 ]. In contrast, a mean age of 56 years was found in multicenter observational studies in two different countries (from India and Nigeria) [ 11 , 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…2 Inter-item Pearson's correlations. 3,4 Experience and stress item correlations are summated. 5 Improved from 0.729 to 0.743 if the third item for this subscale is deleted.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetic foot ulcer (DFU) is an important complication of diabetes, with an incidence rate of 1-4% and a lifetime risk of 15-25% [1,2]. This condition is defined as an ulceration of the foot associated with diabetic neuropathy which show any grade of ischemia and infection [3]. Moreover, this diabetic complication is often associated with other serious complications such as osteomyelitis and lower limb amputation [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation